A STUDY ON THE UNLAWFUL ACT IN SUBSIDIZED FERTILIZER SALES IN BLANG PIDIE - Wardah Wardah; Haikal Maulidy; Muhammad Insa Ansari (Universitas Syiah Kuala, 2022)
Article 1365 of the Indonesian Civil Code states that a tort is an agreement resulted from the law due to a legal violation. In subsidized fertilizer sales, a tort has been committed by business owners who sold the product beyond its price ceiling in Blang Pidie subdistrict, Aceh Barat Daya District. This legal violation has resulted in customer shortfall. The objective of this study was to explain the factors motivating the business owners to sell the subsidized fertilizer beyond its price ceiling, the legal effect of their legal violation, and government efforts to minimize the violation. This research falls under the empirical legal study, and the data were collected using library research and interview with respondents. The collected data were analyzed using the qualitative data analysis method. Based on the research result, the tort was committed for higher profit generation, prepaid income, limited supply, customer ignorance of price ceiling policy, transportation expenses. The legal effect of the unlawful act was that the business owners were obliged to compensate the customers. The government issued a warning to the subsidized fertilizer distributors or terminated their contract with an obligation to compensate the customers.